# math

posted by
**cheryl**
.

-4(2x-3)=-8x+5

Hi Cheryl!

The first thing you have to do with this is multiply the -4 into the stuff in the parenthesis.

-4*2x = -8x

-4*-3 = +12

So the left side is -8x+12 = -8x +5

Now that I'm this far along, we see that there's no real answer to this. If we add -8x to both sides, we get:

12=5. And that's clearly wrong.

Either the book/paper/whatever made a mistake in typing this or they are trying to show this question won't work.

So this was a very good question to put up here because it simply doesn't work. Since you had trouble with it, it looks like you probably did it correctly ;-)